Laboratory operations excellence workshop 2023 / Ms. Kathleen J.Jalani and Dr. Gurmeet Kaur Surindar Singh - J.Jalani, Kathleen; Surindar Singh, Gurmeet Kaur (Faculty of Pharmacy, 2023)
The Laboratory Operations Excellence Workshop was successfully conducted on February 27, 2023, at the Gallery, FF1 Building, Faculty of Pharmacy, UiTM Puncak Alam Campus. The operations excellence (OE) workshop was conducted by an experienced OE trainer, ASP/PB Mohd Tarmizi Abdul Raman. The workshop was aimed at introducing OE to all laboratory staff and applying innovations and changes in laboratory procedures to the daily work process. The session included seminars and group discussions about strengthening laboratory management, refining the P05 procedure on laboratory management and equipment maintenance, and standardising the delivery of information and its implementation.